2000
DOI: 10.2223/jped.172
|View full text |Cite
|
Sign up to set email alerts
|

Basis of nutritional support in pediatrics

Abstract: ResumoObjetivo: Apresentar uma revisão sistemática e atualizada sobre os princípios gerais do suporte nutricional em Pediatria, salientando-se a importância da nutrição no paciente gravemente enfermo.Métodos: Foi realizada a seleção dos estudos relevantes, a partir de vários bancos de dados (Medline, Scielo, Lilacs, etc.), bem como de capítulos de livros e teses a respeito do assunto, além de levar-se em conta a experiência pessoal de cada um dos autores.Resultados: A terapia nutricional é parte integrante do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…11 On the other hand, we omit the LHC jet data, since at the lowest p T measured the threshold corrections are not stable and, moreover, have large uncertainties at the highest rapidities observed. This is slightly more blunt, but quite similar in practice to the conclusion of [124] which compares the degree of agreement between the approximate threshold calculation and the exact calculation for the gg → gg channel, where the later is known. It is found that the agreement is good for high values of p T (relative to centre of mass energy √ s) and relatively central rapidity.…”
Section: Lhc Data On Jetssupporting
confidence: 68%
“…11 On the other hand, we omit the LHC jet data, since at the lowest p T measured the threshold corrections are not stable and, moreover, have large uncertainties at the highest rapidities observed. This is slightly more blunt, but quite similar in practice to the conclusion of [124] which compares the degree of agreement between the approximate threshold calculation and the exact calculation for the gg → gg channel, where the later is known. It is found that the agreement is good for high values of p T (relative to centre of mass energy √ s) and relatively central rapidity.…”
Section: Lhc Data On Jetssupporting
confidence: 68%